2021
DOI: 10.1002/acm2.13255
|View full text |Cite
|
Sign up to set email alerts
|

The application of metal artifact reduction methods on computed tomography scans for radiotherapy applications: A literature review

Abstract: Metal artifact reduction (MAR) methods are used to reduce artifacts from metals or metal components in computed tomography (CT). In radiotherapy (RT), CT is the most used imaging modality for planning, whose quality is often affected by metal artifacts. The aim of this study is to systematically review the impact of MAR methods on CT Hounsfield Unit values, contouring of regions of interest, and dose calculation for RT applications. This systematic review is performed in accordance with the PRISMA guidelines; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 99 publications
1
22
0
Order By: Relevance
“…In case of adjuvant radiotherapy, it is important to provide zygomatic implantspecific information to the radiotherapy team. This enables adjustments of the radiotherapy treatment plan and the dosimetric accuracy in radiotherapy [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In case of adjuvant radiotherapy, it is important to provide zygomatic implantspecific information to the radiotherapy team. This enables adjustments of the radiotherapy treatment plan and the dosimetric accuracy in radiotherapy [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, different implant types were shown to respond differently to DECT and projection-based algorithms with varying MAR efficacy; a combination of the two provided the best artifact suppression from spine implants [91]. While these MAR techniques are useful for followup imaging post instrumentation in MSCC, a recent systemic review showed that they have a limited role in radiotherapy applications due to various factors including the introduction of additional artifacts, and more research is needed to overcome these limitations [92]. While projection-based MAR algorithms address artifacts related to photon starvation, DECT can be utilized to reduce beam hardening artifacts without significant additional radiation exposure [37,77,86,87].…”
Section: Challenges Of Ct: Metal-related Artifactsmentioning
confidence: 99%
“…[1][2][3] Existing methods have demonstrated improved image quality such as reduced standard deviation, improved CT number accuracy, and improved subjective image quality evaluation. 3 However, existing methods can result in residual artifacts and CT number inaccuracies. [1][2][3][4][5][6][7] Many different approaches have been proposed for reducing metal artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous metal artifact reduction methods have been proposed and clinically implemented to reduce the severity of metal artifacts 1–3 . Existing methods have demonstrated improved image quality such as reduced standard deviation, improved CT number accuracy, and improved subjective image quality evaluation 3 . However, existing methods can result in residual artifacts and CT number inaccuracies 1–7 …”
Section: Introductionmentioning
confidence: 99%